Strategi Manajemen Pemasaran Dalam Era Digital Pada Masa Sekarang - Zaenal Abidin; Ahmad Sofyan (Khidmatussifa: Journal of Islamic Studies, 2023)
People frequently utilize the internet in different kinds of settings, such as for work, school, and shopping (also known as online). Investors and other people are not deterred from moving forward by the present. We can utilize or grow organizations that have declined due to an epidemic thanks to the internet. Recent technological developments have indicated a global transformation. Advertising control in the modern digital age does not mean changing physical stores or turning regular stores into online stores. In a higher first-class, crook control flow marketing facilitates. In this day of technology and data, it is crucial to understand how far we have come in achieving the targets set for us. Today, knowledge is a capital in the advancement of technological know-how and a tool for building a nation in the era of globalization in the field of advertising management. Digital media is a tool for developing their operations, particularly in the sphere of advertising, but there is now still a lack of public awareness or marketers in marketing management. Keywords : Marketing, Management, Digital, Field